USE OF CELL SELECTION IN OBTAINING STRESS RESISTANT TOBACCO (NICOTIANA TABACUM L.) TO DELIPIDATED SALINITY AND ANTHROPOGENIC POLLUTION (Ecological Bulletin of Kryvyi Rih District, 2025)
Soil salinity is one of the environmental factors that lead to a significant reduction in plant yields. Due to the overall deterioration of the global environmental picture and the widespread use of artificial irrigation, there is a growing need to breed salt-resistant plant species. The use of plant cell culture also makes it possible to study stress resistance. The advantage of in vitro testing of plant resistance to abiotic factors is the rapid assessment of polygenic resistance. The use of the cell selection method with the application of lethal doses of IPM is a guaranteed method of isolating cell cultures that are characterised by active vital activity under the influence of such a stress load. The tobacco cell lines resistant to barium cations (Ba-CCL) were obtained. The frequency of isolation of resistant variants in any genotype corresponded to the order of 10-6. In cell breeding, resistance is assessed by the relative increase in callus biomass (∆m), which indicates the degree of vital activity (stress damage). The applied concentration of Ba2+ cations was lethal for wild-type cell cultures.  The obtained resistant cultures were considered to be resistant tobacco cell lines, which was proved by further results. They were characterised by stable proliferation under the influence of stressor ions and retained this feature in cell generations after prolonged cultivation without selective pressure.
Keywords: salinity, cell selection, resistance, Nicotiana tabacum L., stress tolerance, K+ and Na+ ions, regenerant, ptotein, lines